Analysis of Work Motivation and Organizational Culture at the CV Oedi Karya Sumedang - Amanda, Helles; Meiqi, Yusi Nur Khoiruni (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
This research focuses on work motivation and organisational culture at CV. Oedi Karya Sumedang. The purpose of this research is to find out how the implementation of work motivation at CV Oedi Karya Sumedang, how the implementation of organisational culture at CV Oedi Karya Sumedang and how the problems and solutions for work motivation and organisational culture at CV Oedi Karya Sumedang. The method used in this research is qualitative research method. The informants in this research are president director, operational director, adm & finance, interior desainer, field officer, workshop furniture, dan workshop interior. The results of this research are that the company in the motivation has been good in terms of physiological needs, security needs, social needs, self-esteem needs and self-actualisation needs. Work Motivation problems are that the infrastructure is inadequate, there is no security guard for security, and there is no training. Organisational Culture in the company answers well regarding aggressiveness, self-awareness, personality, team orientation and performance. Organisational culture problems are that the less active employees new ideas, the personality of mutual respect and respect for the problem is in the field sometimes there is neglect of instructions or frequent arguments, employee innovation is lacking, delays and still frequent miscommunication